Knowledge of Physical Education Students about Tooth Avulsion Before and After Receiving an Informative Leaflet - Gaiotto, Juliana da Silveira [UNESP]; Tanaka, Marcia Hiromi; Castro, Marcelo Fernandes de; Oliveira, Jasiel de; Zuanon, Angela Cristina Cilense [UNESP]; Kimura, Juliana Sayuri (My University, 2024)
Objective: To evaluate the knowledge of Physical Education students about tooth avulsion (TA) in both dentitions before and after receiving an informative leaflet (IL). Material and Methods: The questionnaire contained information about TA in dentition and its management and was applied to the Physical Education students before and after reading an IL. Results: A total of 118 students, 96.61%, attended a first aid course, and 17.80% received information about TA. Most students (88.98%) never had an experience with TA, and 90.68% considered its management important. The other questions, before and after reading the IL, respectively, were: would not perform deciduous tooth replantation (42%; 88%); knew how to handle the avulsed permanent tooth (APT) (38%; 92%); knew how to clean the APT (50%; 99%); knew that permanent tooth replantation (PTR) must be immediate (15%; 95%); knew the ideal time to seek for the dentist right after TA without performing PTR (6%; 83%); knew how to store APT (31%; 97%). Conclusion: The knowledge of Physical Education students in this research revealed a limited understanding of dental tooth avulsion. After receiving an informative leaflet, the students showed a significant improvement in knowledge about traumatic avulsion management, including tooth replantation and proper actions.
Keywords: Dentition, Permanent; Tooth Avulsion; Tooth Injuries; Tooth, Deciduous